Extension and application of dynamic mechanical analysis for the estimation of spatial distribution of material properties. (July 2016) - Kostka, P.; Holeczek, K.; Höhne, R.; Filippatos, A.; Modler, N.
Abstract: The paper presents a unique extension and application of the dynamic mechanical analysis (DMA) technique for the determination of heterogeneous mechanical material properties. Their values as well as their spatial distribution are major interest when analysing properties of post-damage materials. The proposed procedure incorporates longer than typical beam-shaped test samples enclosing the zone with locally varied material properties. The mechanical properties are estimated for the extended sample at defined positions while the sample is iteratively shifted along its axis. The procedure was successfully validated in various tests incorporating standardised and extended samples. The preliminary investigations regarding the application of the proposed procedure were conducted on composite specimens with heterogeneous distribution of material properties introduced by impact load. The results show, on the one hand, a monotonic relation between the storage modulus and the damage extent. On the other hand, a non-monotonic relation between the loss modulus and damage severity has been observed.